NILAI-NILAI PENDIDIKAN KARAKTER PADA MATERI AJAR PENDIDIKAN LINGKUNGAN HIDUP UNTUK SEKOLAH DASAR/ MADRASAH IBTIDAIYAH KELAS II - Karmila, Nita; Indriani, Rini Sri (Program Pendidikan Guru Sekolah Dasar Universitas Pakuan, 2019)
This a qualitative reasearch with a content analysis approach. The object of research is presenting the contents of books and sentences which contain the values of character education. The purposes of this study are 1) Describing the presentation characteristics of the teaching material for Environmental Education Books for 2nd grade of Sd/MI, 2) Exploring the content of character education values in teaching materials for Environmental Education Books for 2nd grade of SD/MI. The research used see and note techniques for data collection. The researcher using triangulation for data validit testing techniques. The conclusions of this research are 1) the characteristics of presenting environmental educations textbooks for 2nd grade of SD/MI compiled by the Bandung PLH team from aspects of content, language, and graphics feasibility have fulfilled good textbooks according to BSNP. However, charachter values need to be re-develoved in each sub-chapter to support the education program. 2) the values of character education contained in the teaching materials for environmental education for 2nd grade of SD/MI compiled by the Bandung PLH team are 1) religious, 2) discipline, 3) creative, 4) environemntal concern 5) social care, and 6) responsibility.